2022
DOI: 10.3390/healthcare10010108
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Frailty in the Middle East: Systematic Review and Meta-Analysis

Abstract: (1) We aimed to systematically search available data on the prevalence of frailty among community-dwelling elders in Middle Eastern countries. The results from available studies are cumulated to provide comprehensive evidence for the prevalence of frailty. (2) Methods: A meta-analysis was done. A literature search was carried out using PRISMA guidelines in PubMed, Web of Science, and SCOPUS websites for studies up to 2020. Inclusion criteria entailed all primary studies conducted in Middle Eastern countries on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…While these changes occur in all individuals as they age, they are particularly pronounced in the frail [42]. A meta-analysis by Bader A A et al, involving nine observational studies, concluded that frailty prevalence is higher in Middle Eastern countries [43].…”
Section: Discussionmentioning
confidence: 99%
“…While these changes occur in all individuals as they age, they are particularly pronounced in the frail [42]. A meta-analysis by Bader A A et al, involving nine observational studies, concluded that frailty prevalence is higher in Middle Eastern countries [43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies were classified as poor [0–4], satisfactory [5–6], good [7–8], or very good [9–10]. Studies with minimal bias were given a maximum of five stars, and the total score ranged from 0 to 10 ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although reliable estimations are difficult to obtain due to extreme variability in the methodological approach adopted in the different studies,[ 26 ] the distribution of the patterns above among the surgical population worldwide is widely influenced by social and economic factors, with higher concentration of disabilities in poorest countries. [ 27 28 ] A correlation between different age brackets and FS with the surgical outcome in the very elderly (aged more than 85 years) has been shown in a wide patients’ group. [ 29 ]…”
Section: Introductionmentioning
confidence: 99%